Calvin"s election mix in small-scale theology - Loader, James Alfred (HTS teologiese studies, 2009)
This paper shows how Calvin’s ideas about the Old Testament concept of Israel’s election can be dangerous when they are applied uncritically. The main illustration material is drawn from a context the author was himself part of, notably the South African apartheid theology of Calvinist provenance. The paper begins with documenting Calvin’s views on Israel and Israel’s election in the Old Testament, moving to a consideration of how this motif was connected to the idea of predestination and construed to become an instrument to defend apartheid in what may be called a substandard theology. It is suggested that a glance at the English-speaking world shows surprising similarities that justify further consideration. In this title several dimensions are present that need to be explicated.